Effect of horse riding equipment in activity of trunk and lower limb muscles in equine-assisted therapy - Janaine Brandao Lage; Mariane Fernandes Ribeiro; Vicente de Paula Antunes Teixeira; Rodrigo César Rosa; Alex Abadio Ferreira; Ana Paula Espindula (Acta Scientiarum. Health Sciences, 2020)
Equine-assisted therapy uses the horse in rehabilitation and/or education of people, such as Down syndrome (SD), cerebral palsy (PC) and intellectual disability (DI). In context, the rehabilitation program and horse riding equipment should be used according to the specific characteristics of each individual, becoming an ally in the quest for excellence in equine-assisted therapy programs. The aim was to evaluate the effect of riding equipment used in equine-assisted therapy on the muscular activity of trunk and lower limb of individuals with SD, PC and DI. The study included 15 individuals equally assigned to each group: SD, PC and DI with a mean age of 16.2 (± 1.10), 16 (± 1.22) e 16 (±0) years, respectively. The analysis of muscle activity was performed through surface electromyography, using four variations of horse riding equipment: saddle with and without feet supported on the stirrups and blanket with and without feet supported on the stirrups. Sigma Stat 3.5® software was used for statistical analysis. The Shapiro Wilk’s test was used for normality of the data, the Bartlett test for homogeneity of the variances and the Kruskal-Wallis test for repeated measures with no normal distribution. Statistically significant differences were observed for p < 0.05. The SD group presented a greater muscular activity of trunk and lower limbs with blanket equipment without the feet supported in the stirrups (H = 15.078, p = 0.002), as in the DI group (H = 8.302, p = 0.040), while in PC group was the saddle with feet supported in the stirrups (H = 11.137, p = 0.011). The choice of riding equipment used in equine-assisted therapy interferes differently in the pattern of muscular activation of the trunk and the lower limbs, according to the pathological processes of the practitioners. It should be an important aspect to consider when planning a treatment.